1994
DOI: 10.1007/bf01552723
|View full text |Cite
|
Sign up to set email alerts
|

A tandemly repetitive, centromeric DNA sequence from the Canadian woodland caribou (Rangifer tarandus caribou): Its conservation and evolution in several deer species

Abstract: A highly repetitive DNA clone, designated Rt-Pst3, was isolated from the PstI digest of Canadian woodland caribou (Rangifer tarandus caribou; 2n = 70) genomic DNA. It was found to be a 991 bp monomer of a tandemly repeated DNA sequence comprising about 5.7% of the genome and localized to the centromeric regions of all caribou acrocentric autosomes. Southern blot analyses revealed that this caribou satellite DNA sequence was well conserved in the genomes of five other deer species studied. In situ hybridization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
37
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 29 publications
2
37
0
Order By: Relevance
“…Some studies suggested that the repetitive DNA families at or near the centromeric and telomeric regions might facilitate illegitimate recombination between non-homologous chromosomes of muntjacs (Brinkley et al, 1984;Bogenberger et al, 1985Bogenberger et al, , 1987Benedum et al, 1986;Lin et al, 1991Lin et al, , 2004Lee et al, 1994Lee et al, , 1997Scherthan, 1995;Lee & Lin, 1996;Yang et al, 1997b;Li et al, 2000aLi et al, , b, 2002Hartmann & Scherthan, 2004). At present, four satellite DNA families are found in Muntiacus: satellite DNA families I, II, IV and V (Bogenberger et al, 1985;Lin et al, 1991Lin et al, , 2004Li et al, 2000bLi et al, , 2005.…”
mentioning
confidence: 99%
“…Some studies suggested that the repetitive DNA families at or near the centromeric and telomeric regions might facilitate illegitimate recombination between non-homologous chromosomes of muntjacs (Brinkley et al, 1984;Bogenberger et al, 1985Bogenberger et al, , 1987Benedum et al, 1986;Lin et al, 1991Lin et al, , 2004Lee et al, 1994Lee et al, , 1997Scherthan, 1995;Lee & Lin, 1996;Yang et al, 1997b;Li et al, 2000aLi et al, , b, 2002Hartmann & Scherthan, 2004). At present, four satellite DNA families are found in Muntiacus: satellite DNA families I, II, IV and V (Bogenberger et al, 1985;Lin et al, 1991Lin et al, , 2004Li et al, 2000bLi et al, , 2005.…”
mentioning
confidence: 99%
“…Cell lines, chromosome preparations, and DNA isolation Metaphase chromosome spreads and genomic DNAs were prepared from the fibroblast cell lines of the following species: Indian muntjac (Muntiacus muntjak vaginalis) (male cell line, CCL-157, American Type Culture Collection; female cell line, kindly supplied by Dr. Andrew P. Feinberg, School of Medicine, Johns Hopkins University, Baltimore, MD, USA); Formosan muntjac (M. reevesi micrurus) ; caribou (Rangifer tarandus caribou) (Lin et al 1991;Lee et al 1994;Lin et al 2004); male black-tailed deer (Odocoileus hemionus hemionus) (CRL-6193, American Type Culture Collection); female Chinese water deer (Hydropotes inermis) (kindly provided by Dr. F. Yang, Centre for Veterinary Science, University of Cambridge, Cambridge, UK); Roe deer (Capreolus capreolus capreolus) cell line (from San Diego Zoo, San Diego, CA, USA) and male Formosan sambar deer (Cervus unicolor swinhoei) (Li et al 2005). Metaphase chromosome spreads and genomic DNAs of Formosan sika (Cervus nippon taioanus) and Asian red deer (Cervus elaphus) were prepared from blood samples provided by a certified deer farm in Taiwan.…”
Section: Methodsmentioning
confidence: 99%
“…We used the 32 P-labeled insert fragment of satVI-1C5 to probe the nylon membrane. The dot blot hybridization procedure has also been described elsewhere (Lee et al 1994;Li et al 2000a). A copy number was roughly estimated from the signal intensity of a control plasmid satVI-1C5 DNA (0.195 ng; approximately 0.054 ng of insert) that showed similar signal intensity as the genomic DNA (3.125 ng for male Indian muntjac and male Formosan muntjac each; 100 ng for male Sambar deer).…”
Section: Southern Blot Zoo Blot and Dot Blot Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the horse chromosomes, tandem repeat elements have been localized only in the centromeres of the acrocentrics, not in the metacentrics (Broad et al, 1995). Centromeric satellite probes have been obtained for many other species including rabbit (Ekes et al, 2004), roe deer (Buntjer et al, 1998) and caribou (Lee et al, 1994).…”
mentioning
confidence: 99%